1991
DOI: 10.1177/088626091006001007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sexual Provocativeness, Rape History, and Observer Gender in Perceptions of Blame in Sexual Assault

Abstract: To assess joint influence of sexual provocativeness and prior sexual assault on perceptions of rape victims, males and females read rape reports presented in a factorial design that completely crossed levels of these variables. Multivariate analysis of variance indicated main effects for the independent variables but no interactions. Observers attributed more blame to victims whose preassault behavior was more provocative and who had a prior rape history. Relative to males, females were generally more empathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 14 publications
5
54
0
Order By: Relevance
“…Previous research has suggested that in interpersonal situations, perceived similarity leads to more generous attributions, regardless of outcome (e.g. Calhoun, Selby & Warring, 1976;Arkin, Gabrenya & McGarvey, 1978;Kanekar & Kolsawalla, 1981;Kanekar, Pinto & Mazumdar, 1985;Schult & Schneider, 1991). When two people perceive themselves to be similar to each other along some dimension, they will not only give each other more credit for successful outcomes, but they will also take more responsibility for failed outcomes.…”
Section: The Self-serving Biasmentioning
confidence: 94%
“…Previous research has suggested that in interpersonal situations, perceived similarity leads to more generous attributions, regardless of outcome (e.g. Calhoun, Selby & Warring, 1976;Arkin, Gabrenya & McGarvey, 1978;Kanekar & Kolsawalla, 1981;Kanekar, Pinto & Mazumdar, 1985;Schult & Schneider, 1991). When two people perceive themselves to be similar to each other along some dimension, they will not only give each other more credit for successful outcomes, but they will also take more responsibility for failed outcomes.…”
Section: The Self-serving Biasmentioning
confidence: 94%
“…First, male participants attribute greater responsibility to a victim of rape than female participants judging the same vignette (Bell et al 1994;Brems and Wagner 1994). Second, male participants are more likely to rate the victim as provoking the assault (Szymanski et al 1993), and inviting the sexual behavior (Schult and Schneider 1991) than female participants.…”
Section: Introductionmentioning
confidence: 97%
“…In the first task, participants read a mock police file and then answered questions relating to the perceived innocence and guilt of the survivor (CRQ; Schult & Schneider, 1991). In addition to these measures, participants completed an open-ended question immediately after reading the scenario.…”
Section: Methodsmentioning
confidence: 99%
“…The Case Reaction Questionnaire (CRQ; Schult & Schneider, 1991) included nine questions that measured participants' perceptions of both survivor (''To what extent do YOU think [the survivor's] behavior contributed to the rape?'') and perpetrator blame (''If [the survivor] had come to talk to you, how much would YOU want [the survivor] to blame what happened on the assailant?'').…”
Section: Methodsmentioning
confidence: 99%